Adalimumab‐Induced Cutaneous Lupus Erythematosus: Cases Presenting With Malar Rash and Panniculitis - Parvin Mansouri; Farahnaz Bidari‐Zerehpoosh; Nikoo Mozafari (Clinical Case Reports)
ABSTRACT Tumor necrosis factor‐alpha (TNF‐α) inhibitors are commonly used for management of various autoimmune disorders but can rarely cause isolated cutaneous lupus. This report presents two cases of cutaneous lupus erythematosus (LE) in women aged 38 and 61 after adalimumab treatment for psoriasis highlighting the importance of recognizing these paradoxical reactions for timely management.